Increasing Teacher Competency in Learning Innovation through Coaching-Based Learning Communities (JURNAL ILMIAH TUT WURI HANDAYANI, 2024)
Teacher competence in delivering relevant and effective learning innovations plays a critical role in improving education quality. However, many educators struggle to develop and implement creative teaching strategies consistently. This study investigates how coaching-based professional learning communities (PLCs) contribute to enhancing teachers’ competence in innovative pedagogical practices. Employing a literature review and analysis of best practices, the study explores the integration of structured coaching, peer collaboration, and reflective dialogue within PLCs. The coaching model emphasized continuous feedback, contextual problem-solving, and shared experiences among educators. Findings suggest that such communities foster pedagogical transformation by supporting teachers’ capacity to design student-centered, creative learning activities aligned with classroom needs. The coaching process not only builds technical skills but also encourages deep reflection, strengthening professional growth through a collaborative culture. This study concludes that coaching-based PLCs offer a sustainable approach to bridging the gap between theoretical training and classroom practice. The contribution of this research lies in its practical framework for advancing teacher competency through experiential, contextual, and collegial support systems.